Studies on pharmaceutical ethnobotany in Arrábida Natural Park (Portugal) - Novais, Maria Helena (2004)
An ethnobotanical survey was carried out in Arrabida Natural Park, a Portuguese Protected Area in the Southwest of the Iberian Peninsula, with an area of 10 820 ha.Working with 72 local people, data on medicinal uses of 156 taxa, belonging to 56 botanical families, were obtained and presented, of which 214 uses corresponding to 81 taxa were previously unreported.